2015
DOI: 10.1016/j.eatbeh.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between disordered eating and sexuality amongst adolescents and young adults

Abstract: Research shows that gay and bisexual males are at increased risk for disordered eating symptoms (DES); however, studies examining DES amongst lesbians and bisexual women have produced mixed findings. Furthermore, few studies have included questioning or "unsure" individuals. This study examined DES symptoms in adolescents and young adults across self-reported sexual attraction and behavior. Participants were recruited from ten primary care sites in Pennsylvania and administered the Behavioral Health Screen (BH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
(51 reference statements)
2
29
0
Order By: Relevance
“…As regards eating concerns, the literature has shown conflicting results as well, which has made difficult to estimate any eventual difference between SM women and heterosexual women. Maloch et al () and Shearer et al () found greater eating concerns only in bisexual women compared with heterosexual women. Strong et al () and Share and Mintz () did not find any differences between the populations studied, whereas Meyer et al () found greater concerns about eating in heterosexual women with a direct correlation with femininity, and Siever () found fewer eating worries in homosexual women than in heterosexual ones.…”
Section: Resultsmentioning
confidence: 94%
“…As regards eating concerns, the literature has shown conflicting results as well, which has made difficult to estimate any eventual difference between SM women and heterosexual women. Maloch et al () and Shearer et al () found greater eating concerns only in bisexual women compared with heterosexual women. Strong et al () and Share and Mintz () did not find any differences between the populations studied, whereas Meyer et al () found greater concerns about eating in heterosexual women with a direct correlation with femininity, and Siever () found fewer eating worries in homosexual women than in heterosexual ones.…”
Section: Resultsmentioning
confidence: 94%
“…samples have yet to be established among sexual minorities, research has begun to explore trends in ED symptoms and behaviors among these groups. Within this area of research, those identifying as a sexual minority report greater frequencies of symptoms or features of EDs compared to their heterosexual counterparts (French, Story, Remafedi, Resnick, & Blum, 1996;Laska et al, 2015;Shearer et al, 2015).…”
Section: Although Prevalence Estimates Of Eds In Nationally Representmentioning
confidence: 99%
“…Studies utilizing such instruments and aggregate measures of symptoms (e.g., aggregating vomiting, laxatives, diet pill use into a “unhealthy weight control” variable[25]) have found that sexual minority men and women report greater levels of overall symptoms than their same gender heterosexual peers, although disparities among men are more consistent across studies. [2528] For example, Shearer and colleagues examined sexual orientation disparities in overall symptoms in a youth sample (ages 14–24) from Pennsylvania and found that males who reported same-gender attractions had higher symptoms than those who reported other-gender attractions; among females, those attracted to both genders had higher symptoms than those who reported other-gender or same-gender attractions, and those unsure of their attractions reported the highest symptoms of all. [28] However, in Yean et al’s multi-site study of community and university participants, gay and bisexual men had higher scores than heterosexual men on the EAT-26, whereas no difference was detected between lesbian and bisexual women and heterosexual women.…”
Section: Epidemiologic Surveillancementioning
confidence: 99%
“…[2528] For example, Shearer and colleagues examined sexual orientation disparities in overall symptoms in a youth sample (ages 14–24) from Pennsylvania and found that males who reported same-gender attractions had higher symptoms than those who reported other-gender attractions; among females, those attracted to both genders had higher symptoms than those who reported other-gender or same-gender attractions, and those unsure of their attractions reported the highest symptoms of all. [28] However, in Yean et al’s multi-site study of community and university participants, gay and bisexual men had higher scores than heterosexual men on the EAT-26, whereas no difference was detected between lesbian and bisexual women and heterosexual women. [27]…”
Section: Epidemiologic Surveillancementioning
confidence: 99%